Human Rights and Military Health: A Review of Violations of International Criminal Law in Armed Conflict - Hodijatussolihah; Rosidah; Purnomo, Hadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Human Rights (HAM) are rights inherent in every individual, including in the context of military health in the midst of armed conflict. This article reviews violations of International Criminal Law (HPI) that occur in conflict situations, such as murder, torture and forced labor. Protection of human rights in the midst of armed conflict is important, especially regarding access to adequate health services and freedom from treatment that violates human rights. Serious efforts are needed to ensure that military health does not violate human rights principles, so that the world community can maintain their dignity and human rights, even in the midst of conflict-ridden situations